The five : the untold lives of the women killed by Jack the Ripper - Rubenhold, Hallie (Houghton Mifflin Harcourt, 2019)
Polly, Annie, Elizabeth, Catherine and Mary-Jane are famous for the same thing, though they never met. They came from Fleet Street, Knightsbridge, Wolverhampton, Sweden, and Wales. They wrote ballads, ran coffee houses, lived on country estates, they breathed ink-dust from printing presses and escaped people-traffickers. What they had in common was the year of their murders: 1888. The person responsible was never identified, but the character created by the press to fill that gap has become far more famous than any of these five women. For more than a century, newspapers have been keen to tell us that "the Ripper" preyed on prostitutes. Not only is this untrue, as historian Hallie Rubenhold has discovered, it has prevented the real stories of these fascinating women from being told. Now, in this devastating narrative of five lives, Rubenhold finally sets the record straight, revealing a world not just of Dickens and Queen Victoria, but of poverty, homelessness and rampant misogyny. They died because they were in the wrong place at the wrong time<U+2014>but their greatest misfortune was to be born a woman.